Board Director Diversity and Corporate Innovation : A Library Research - Megayanti, Putri; Purnomo, Margo; Purbasari, Ratih (Universitas Indraprasta PGRI Jakarta, 2024)
Diversity among board members tends to foster a knowledge base for the company and encourage interaction between different knowledge and competencies. Diversity can also improve better performance such as creative and innovative ideas, as well as good problem solving. The purpose of this study is to understand the concept of board diversity on corporate innovation. The method used is an exploratory literature study of the results of previous research on board diversity and corporate innovation. The results from various sources show that the diversity of the board of directors in the company has a significant and insignificant effect on corporate innovation.